Judgment and Embodied Cognition of Lawyers. Moral Decision-Making and Interoceptive Physiology in the Legal Field - Angioletti, Laura; Tormen, Federico; Balconi, Michela (Frontiers in Psychology, 2022)
Past research showed that the ability to focus on one’s internal states (e.g., interoceptive ability) positively correlates with the self-regulation of behavior in situations that are accompanied by somatic and/or physiological changes, such as emotions, physical workload, and decision-making. The analysis of moral-oriented decision-making can be the first step for better understanding the legal reasoning carried on by the main players in the field, as lawyers are. For this reason, this study investigated the influence of the decision context and interoceptive manipulation on the moral decision-making process in the legal field gathering the responses of two groups of lawyers. A total of twenty lawyers were randomly divided into an experimental group (EXP), which was explicitly required to focus the attention on its interoceptive correlates, and a control group (CON), which only received the general instruction to perform the task. Both groups underwent a modified version of the Ultimatum Game, where are presented three different moral conditions (professional, company, social) and three different offers (fair, unfair, equal). Results highlighted a significant increase of Acceptance Rate (AR) in those offers that should be considered more equal than fair or unfair ones, associated with a general increase of Reaction Times (RTs) in the equal offers. Furthermore, the interoceptive manipulation oriented the Lawyers towards a more self-centered decision. This study shows how individual, situational, contextual, and interoceptive factors may influence the moral decision-making of lawyers. Future research in the so-called Neurolaw field is needed to replicate and expand current findings.